Efficacy of different entomopathogenic fungal isolates against four key stored-grain beetle species. (September 2021) - Wakil, Waqas; Kavallieratos, Nickolas G.; Ghazanfar, Muhammad Usman; Usman, Muhammad; Habib, Amer; El-Shafie, Hamadttu A.F.
Abstract: The development of resistance in stored-grain insect pests can be effectively reduced by using biological control methods. Entomopathogenic fungi have been under consideration as complementary and alternative agents to synthetic insecticides. The aim of this study is to identify the pathogenic potential of four different fungal isolates of Beauveria bassiana (Bals.-Criv.) Vuill. (Hypocreales: Cordycipitaceae) (WG-47, WG-48, WG-50, WG-51) and three isolates of Metarhizium anisopliae (Metchnikoff) Sorokin (Hypocreales: Clavicipitaceae) (WG-46, WG-49, WG-52) against the adult stages of the lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae), the granary weevil, Sitophilus granarius (L.) (Coleoptera: Curculionidae), the red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) and the khapra beetle, Trogoderma granarium Everts (Coleoptera: Dermestidae) at 1 × 10 6, 1 × 10 7, 1 × 10 8 and 1 × 10 9 conidia/kg wheat. Mortality was found dose dependent among all the tested species. Rhyzopertha dominica was the most susceptible followed by S. granarius, T. castaneum and T. granarium . Among the different isolates B. bassiana caused higher mortality compared to M. anisopliae . The isolates WG-50 and WG-51 of B. bassiana provided maximum mortality among the different tested species and led to lower F1 individuals compared to the controls. Our study indicates that entomopathogenic fungi have an elevated potential to successfully manage the aforementioned coleopteran species on stored wheat. Highlights: B. bassiana isolates caused higher mortality compared to M. anisopliae isolates. Fungal isolates caused the highest mortality to R. dominica and least to T. granarium . B. bassiana WG-50 and WG-51 isolates provided maximum mortality among tested species. WG-50 and WG-51 isolates caused maximum reduction of progeny production of all beetles.